Anesthetic Management with Intubation in Awake Patient with Ludwig’s Angina Using Dexmedetomidine and Ketamine: A Case Report - Esquivel-Diaz, Francisco Rodolfo; Hernández-Flores, Silvia; Noguera Echeverría, Alexis Emir; Ibarra-Guerrero, María Fernanda; Islas-Canto, Víctor Rodrigo (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Ludwig’s Angina (LA) is a bacterial infection of the submandibular space that can cause airway obstruction. Prompt surgical treatment and antimicrobial therapy are crucial. Airway evaluation is important to identify risk factors for difficult intubation and anatomical distortion that may require awake endotracheal intubation. Case presentation: A 22-year-old female presented to the emergency department with left submandibular pain, edema, increased skin temperature, and erythema with a history of grade III caries of 6 months evolution without treatment. Physical examination revealed extension to the left lateral neck region and mild respiratory distress. Classified as ASA grade III, the patient underwent awake intubation using dexmedetomidine (DXM) and ketamine (KET), followed by balanced general anesthesia for the surgical procedure. Clinical discussion: The patient’s condition predicted high difficult airway, therefore awake intubation was performed to maintain spontaneous ventilation and reduce cardiac arrest risk. In this case, DXM was used to avoid anxiety and respiratory depression, while KET was employed for its analgesic, bronchodilator, and tachycardic effects. Conclusion: Ketamine and dexmedetomidine allow adequate spontaneous ventilatory mechanics, without respiratory depressant effect. Further research is needed to find more anesthetic drugs that can be used for intubation without suppressing autonomic ventilation, and to develop guidelines to prevent respiratory depressant effects in patients with LA.